Redescription of the highly specialized aquatic †Tigrivia and the classification of the Mesozoic †Coptoclavidae (Coleoptera, Adephaga, Dytiscoidea) - Bao, Liang; Beutel, Rolf Georg; Niu, Kecheng; Bao, Tong (Zootaxa, 2025)
†Tigrivia baii, a highly specialized aquatic beetle assigned to the adephagan †Coptoclavidae, is redescribed and documented in detail. The observed morphological features are discussed with respect to function, phylogenetic significance, and the current classification of the Mesozoic family. Cladistic analyses indicate that †Tigrivia is the sister taxon of †Coptoclava. Both may be closely related with †Daohugounectes, but this was not confirmed by the analyses. †Tigrivia is a highly specialized genus, more advanced than the closely related †Coptoclava, showing a range of features suggesting evolutionary parallels with Gyrinidae, i.e. long raptorial forelegs, a very small prosternal process, an unusually large mesoventrite without hexagonal groove, apically truncated elytra, and exposed appendices of abdominal segment VIII. However, a detailed assessment of these features and the phylogenetic analysis revealed that these derived characteristics have evolved independently in †Tigrivia and whirligig beetles. †Tigrivia and other beetles in †Coptoclavidae were likely facultative surface hunters, but less specialized than Gyrinidae, which can swim rapidly on the surface film with paddle-like short middle and hind legs. In any case †Tigrivia and †Coptoclava were active predators, likely preying on small fishes and amphibian larvae. †Coptoclavidae is not monophyletic, and the same is probably true for most of the subfamilies, especially †Necronectinae (= †Timarchopsinae). While many coptoclavid taxa display subdivided compound eyes with an upper and lower subunit, this feature is not a synapomorphy since it is not found in all genera. Groups with metacoxae of a haliplid or trachypachid type, with the mesal walls not fused and with large posterior plates, apparently do not belong to Dytiscoidea, and should be removed from †Coptoclavidae. The rest of the family, characterized by extensively fused mesal metacoxal walls and largely reduced coxal plates belong to a clade comprising all dytiscoid families except for Noteridae and Meruidae.